TEACHER PROFESSIONAL DEVELOPMENT FOR THE INTEGRATION OF EMI IN ALGERIAN UNIVERSITIES - Kaid, Nassima; Labed, Zohra (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
With the growing spread of English as a Lingua Franca, universities around the world are increasingly offering courses taught in English, the Algerian Minister of Higher Education recently required content teachers to use English as a medium of instruction (EMI) into their classrooms. Nonetheless, the new instruction has led to many apprehensions among these teachers, who must change their mode of instruction at short notice. To ensure a smooth transition, teachers are required to pursue intensive English courses to improve their proficiency. Based on a quantitative method, the study investigates teachers’ attitudes and assessment of professional development sessions in Algerian universities one year after the beginning of the English sessions; it gauges the satisfaction of 125 higher education subject-matter instructors with the pedagogical program offered and discusses its impact on teachers’ English proficiency. The findings revealed that 46% of teachers are enrolled in the English courses and indicated low satisfaction with the implemented program. Furthermore, these valuable results have significant implications for the design of more effective and successful pedagogical training programs in Algerian higher education. Though the findings cannot be generalized, it does include features that instructors might find valuable.